The Deadly Dungeon - Ron Roy
Dink's favorite mystery writer, Wallis Wallace, has invited Dink, Josh, and Ruth Rose for a sleepover - in a haunted castle! But as soon as the young detectives arrive, they start hearing screams behind the walls. Will they discover who - or what - is haunting Moose Manor?